Training of farmers to raise awareness and usage of EzyAgric’s digital innovation bundles - Ategeka, Stewart; Luyinda, William B.; Arach, Zilla M.; Ogutu, Sylvester; Ajambo, Susan; Birachi, Eliud A.; Kikulwe, Enoch M. (International Food Policy Research Institute, 2024)
This technical report presents outcomes of EzyAgric’s digital innovation awareness raising campaigns that aimed to enhance awareness and usage of EzyAgric’s digital innovation bundles among farmers and agro-inputs merchants in Luwero, Nakaseke, and Mityana districts. The objectives included fostering knowledge about EzyAgric's digital products and services, promoting quality assurance of agro-inputs, training on the safe use of agro- chemicals and climate-smart agriculture. Overall, 293 farmers were engaged, including 246 target farmers, and 47 non-target farmers. The training emphasized hands-on activities and practical demonstrations of the EzyAgric digital innovations, actual delivery of agricultural products ordered by the merchants. Key topics covered included agro-input requirements for coffee, maize, banana, tomatoes, and climate smart agriculture practices. The initiative saw a 32% increase in participation due to localized training sessions and the involvement of community leaders. Key achievements include 50 new users onboarded on the EzyAgric App, 246 farmers enrolled on EzyAgric’s USSD platform, and some agro-input sales to the newly onboarded merchants. Major challenges were low smartphone penetration, low digital proficiency among the target farmers, and lack of for- mal farmer organization structures. The next steps include continuous farmer engagement, demand aggregation, and timely supply of quality inputs to farmers and agro-input merchants. The report recommends the utilization of farmer organization structures and localized group training as a scalable approach in awareness raising campaigns on the adoption of digital innovations.